Managerial Accounting Systemization Issues - Gevorgyan, Julietta (Bulletin of Yerevan University G: Economics, 2014)
The article discusses the opportunities of organizing systematized managerial accounting, according to the financial accounting put into practice at present. Implementation of double entry principle in managerial accounting will maintain the systematization of information in decision making and find out cause-effect correlations between business activity and financial status of companies. In this connection, a model of balanced indices information model within managerial accounting system is suggested.
Keywords: managerial accounting, system information, financial status, balanced indices